The tradition of workers' control : selected writings - Ostergaard, Geoffrey, 1926-1990; Bamford, Brian (London : Freedom press, 1997)
In this book Ostergaard sets out to sketch the historical development of the concept of workers' control in Britain, to clarify and assess the significance of the concept, and to explain why, both in theory and in practice, the idea has met with such little success